COMMON FIXED POINT FOR LIPSCHITZIAN MAPPING SATISFYING RATIONAL CONTRACTIVE CONDITIONS - Abbas, Mujahid (Italian Journal of Pure and Applied Mathematics, 2010)
Common fixed point theorems for a class of mappings called occasionally weakly compatible in a symmetric space (X,d) under Lipschitzian type rational contractive conditions are obtained.